If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(y + 2) = 2(y + 4) Reorder the terms: 8(2 + y) = 2(y + 4) (2 * 8 + y * 8) = 2(y + 4) (16 + 8y) = 2(y + 4) Reorder the terms: 16 + 8y = 2(4 + y) 16 + 8y = (4 * 2 + y * 2) 16 + 8y = (8 + 2y) Solving 16 + 8y = 8 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 16 + 8y + -2y = 8 + 2y + -2y Combine like terms: 8y + -2y = 6y 16 + 6y = 8 + 2y + -2y Combine like terms: 2y + -2y = 0 16 + 6y = 8 + 0 16 + 6y = 8 Add '-16' to each side of the equation. 16 + -16 + 6y = 8 + -16 Combine like terms: 16 + -16 = 0 0 + 6y = 8 + -16 6y = 8 + -16 Combine like terms: 8 + -16 = -8 6y = -8 Divide each side by '6'. y = -1.333333333 Simplifying y = -1.333333333
| 15k-3(3k+4)=6 | | 4x-3=2-x-1 | | x^2-13x=60 | | 4y-5=-29 | | 3(r+2)=1 | | 2(X^2+8X-3)=0 | | In(x)=80 | | w^2-5w+7-35=0 | | -15+j=19 | | 20x+48=33x+9 | | lnx=80 | | (2ab)2a-0.5b=1.2 | | 14=x+169 | | 4/5t+2/5=2/3 | | 12x=4(x+10) | | r-(-10.2)=-7.3 | | 9(n-1)=6(y-3) | | 7y-2=14y+26 | | 5(n+2)=5+10m | | 19-(3m+5)=5+2m-11 | | 6p^2+15p-63=3p+3p^2 | | Y+4=3(-1) | | 8(2x-5)-8x=4-4(x-1) | | -3+4=3 | | -144=2y | | 11(11x-7)=-4 | | -7+4(1+6n)=32 | | ((5)(5))+((5)(5))=((c)(c)) | | 7(u-3)-7=-3(-9u+4)-8u | | (y-30)+2y=90 | | -4(2-7d)=5(5-h) | | 0.5x+-3.5=0.2x-0.5 |